Cardiac amyloidosis mimicking acute coronary syndrome: a case report and literature review. Issue 6 (29th October 2020) - Nguyen, Huan T; Nguyen, Chuyen T H
Abstract: Background: Cardiac amyloidosis, a progressive cardiac disease, results from the accumulation of undegraded proteinaceous substrates in the extracellular matrix of the heart. It may present as acute coronary syndrome (ACS); therefore, a clear distinction remains challenging in clinical practice. We describe a case of cardiac amyloidosis mimicking ACS. Case summary: A 72-year-old man experienced chest discomfort for 2 days. He gradually developed dyspnoea during the preceding month. Electrocardiogram (ECG) showed sinus rhythm with right bundle branch block and low voltage. Echocardiography revealed concentric left ventricular thickening, biatrial dilation, and preserved ejection fraction with predominantly left ventricular basal hypokinesis. Serial testing of the cardiac biomarkers showed persistently increased high-sensitive cardiac troponin T levels and normal serum creatine kinase myocardial band levels. He was diagnosed with ACS with haemodynamic stability. However, coronary angiography demonstrated non-obstructive coronary arteries. Furthermore, significant macroglossia and periorbital purpura were noticed. Laboratory investigations revealed elevated serum immunoglobulin free light chain (FLC) kappa and lambda levels with an increased FLC ratio. Histological analysis of the biopsied abdominal skin confirmed amyloidosis. Discussion: Cardiac amyloidosis often presents as restrictive cardiomyopathy. The usual symptoms include dyspnoea and peripheral oedema. Chest pain may manifest rarely, leading to misdiagnosis as coronary artery disease. Some findings suggestive of cardiac amyloidosis include clinical signs such as amyloid deposits, dyspnoea, low ECG voltage, and basal-predominant hypokinesis with relative apical sparing in echocardiography. Serum FLC test and abdominal skin biopsy can confirm the diagnosis of amyloidosis when a myocardial biopsy is not feasible.